Résistances catholiques au protocole de Maputo. Mobilisations et controverses autour de la libéralisation de l’avortement en Afrique - Lison Guignard (Genre, Sexualité et Société)
This article investigates the Catholics opposition to the ratification of the Additional Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Women in Africa (Maputo Protocol). This Protocol states among other things the right of women to medical abortion under certain circumstances in a context where most of sub-Saharan African countries have restrictive abortion laws. Based on a press review and a discourses analysis, this article explores the process of politicization of sexual and reproductive issues by religious actors through the Catholic opposition to the article 14. As such, the controversy stemmed from this resistance shows what is at stake in the liberalization of abortion. In the post-colonial African context, these issues are presented as a Western invasion and lead to specific type of resistant position.